Creation of educational-information technopark as means of socialization of rural schoolboys - Almurzaeva, Bibigul; Shunkeeva, Orynkul; Zhaytapova, Altnay (Przegląd Wschodnioeuropejski, 2017)
The subject of the research within the scientific grant is to determine the degree of socialization of rural schoolboys of Aktobe region of Kazakhstan at information and educational technology park. Theoretical base was the analysis of philosophical, psychological, pedagogical and methodological literature, legal documents, reflecting the activities of small schools. The work used genetic, systemic, structural and interpretive methods. The implementation effectiveness of the research work will allow to include all educational organizations Mugalzharsky district of Aktobe region in the work of education and information Technopark. The issues of transportation of students and their accommodation in the sessional period, power, etc. fade away. With further improvement and elaboration of all sections at Technopark area students will be able to engage in in-depth academic subjects, organize scientific community to share techniques and solutions etc.